Spatio-temporal control of dispersive waves trapping by solitons in graded-index multimode fibers. (14th October 2020) - Deng, Zhixiang; Chen, Yu; Liu, Jun; Zhao, Chujun; Fan, Dianyuan
Abstract: We investigate the impact of the spatial beam oscillations in a graded-index multimode fiber (MMF) upon the trapping and blue-shifting of dispersive pulses by a multimode soliton. We find that the dispersive pulses trapped by solitons can be controlled through adjusting the degree of compression of the spatial beam. This can provide an explanation for the enhanced blue spectral extension observed in the typical supercontinuum generation in graded-index MMFs. Besides, the spatial-temporal nonlinear effect may provide an additional degree of freedom for the spectrally tailored light generation and the ultrashort pulse generation with tunable wavelengths in the normal dispersion regime.